2004
DOI: 10.1103/physrevb.70.165418
|View full text |Cite
|
Sign up to set email alerts
|

Model calculations of superlubricity of graphite

Abstract: In this paper, friction between a finite, nanometer-sized, rigid graphite flake and a rigid graphite surface is analyzed theoretically in the framework of a modified Tomlinson model. Lateral forces are studied as a function of orientational misfit between flake and surface lattices, pulling direction of the flake, flake size and flake shape. The calculations show that the orientation dependence of the friction provides information on the contact size and shape. We find good agreement between the calculations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

21
170
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(194 citation statements)
references
References 23 publications
21
170
2
1
Order By: Relevance
“…The angular width of the friction maxima decreases with the size of the flake. These results are in agreement with the experimental data [3][4][5] and previous quasistatic calculations [4] which provided firm evidence for superlubricity.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…The angular width of the friction maxima decreases with the size of the flake. These results are in agreement with the experimental data [3][4][5] and previous quasistatic calculations [4] which provided firm evidence for superlubricity.…”
supporting
confidence: 83%
“…Detailed experimental studies of superlubricity have been performed recently by Dienwiebel et al [3][4][5], who measured friction between a graphite flake attached to the tip of a frictional force microscope (FFM) and an atomically flat graphite surface. Superlow friction forces (<50 pN) have been found for most relative orientations of the flake and the substrate, for which the contacting surfaces find themselves in incommensurate states.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, at incommensurate interfaces, atomic friction studies revealed a superlubrication regime, where the friction coefficient vanishes 15,16 . This behaviour can be explained by simple mechanical models such as the FrenkelKontorova model, a generalized Prandtl-Tomlinson scheme or the double-chain model [17][18][19][20] . In the Frenkel-Kontorova approach the interface between two solids is described by a monolayer of elastically interacting beads on a periodic substrate potential [5][6][7][8] .…”
mentioning
confidence: 99%
“…10,11 The existence of quadrupole or higher order interactions may cause the super-diffusivity between graphene and graphite observed with atomic force microscopy (AFM). 10,12,13 Interactions of the same nature exist in poly-aromatic hydrocarbons (PAH) adsorbed on graphitic substrates, 14,15 which are characterized by a very low energy barrier for lateral diffusion 16 and can act as nano-sized lubricants. 2 Scattering techniques such as quasi-elastic helium atom scattering (QHAS) and quasielastic neutron scattering (QENS) are powerful tools to investigate very fast molecular dynamics (pico-second time scale and atomistic length scale).…”
mentioning
confidence: 99%